Influence of Membrane Properties on Pineapple Wine Clarification and Fouling Behavior - Youravong, W.; Phukdeekhong, M.; Taksinpatanapong, P. (Journal of Applied Membrane Science & Technology, 2017)
The experiment was carried out to investigate the influence of membrane pore size and hydrophobicity on the quality of clarified pineapple wine and fouling characteristics, using stirred cell dead–end microfiltration. The test membranes were mixed cellulose acetate (MCE, pore size 0.45 and 0.22 μm), modified polyvinylidene fluoride (MPVDF, 0.22 μm) and polyethersulfone (PESF, 0.22 μm). It was found that all types of membrane successfully clarified the pineapple wine. The membrane pore size and hydrophobicity played an importance role in membrane fouling, both reversible and irreversible. Regarding the permeate flux and fouling, 0.45 μm MCE was the most suitable for pineapple wine clarification. However, intensive organoleptic test with pilot scale would be needed.